Changes in specific discharge in the lowland part of Poland in the years 1961–2021 - Świątek, Małgorzata (Acta Geographica Lodziensia, 2024)
The subject of the study was the analysis of changes in water resources in lowland Poland based on the volume of specific discharge from 39 catchments located on coastlines, in lake districts and in lowlands in the hydrological years 1961–2021. The analyses were based on trends in average annual and monthly runoff from individual catchments, taking into account their statistical significance. Catchments were also clustered using the Ward method in terms of the pace of the observed changes (slope trend coefficients) in specific discharges in individual months. Approximately half of the studied catchments showed a significant decrease in average annual specific discharges. None recorded a statistically significant increase in this parameter. Most catchments recorded declines in runoff in the spring months (April and May), and four recorded increase in runoff in the winter months (January and February). The most significant changes in water resources measured by the amount of specific discharge occurred in catchments located in plains characterised by low natural retention and situated within the lowlands.